ETHNOMATHEMATICS: ARITHMETIC SEQUENCE PATTERNS OF MINANGKABAU CARVING ON SINGOK GONJONG - Alghar, Muhammad Zia; Susanti, Elly; Marhayati, Marhayati (Jurnal Pendidikan Matematika (JUPITEK), 2022)
This study aimed to explore the arithmetic sequence pattern found in Minangkabau carvings mounted on singok gonjong. The method used is a qualitative method with an ethnographic approach. Data was collected by observation, interviews, literature studies, and documentation. The object of this study is Minangkabau carving on singok gonjong. The data obtained in this study came fromdirect observation, results of interviews with Minang carving craftsmen, documentation, and literature studies. The results showed three kinds of arithmetic sequence patterns in Minang carvings in singok gonjong. The first is the arithmetic sequence pattern on the saik galamai carving with formula Un = n. The second is the pattern of odd and even arithmetic sequences on the sikambang manih carving wtih the odd formula U(2n+1) = 3n + 1 and the even formula U(2n) = 3n. The last is the pattern of odd and even arithmetic sequences on the combined engraving of saik galamai and sikambang manih wtih the odd formula U(2n+1) = 4n + 1 and the even formula U(2n) = 4n. The conclusion shows that the presence of patterns on the saik galamai carvings and sikambang manih carvings found on Singok Gonjong can be used as a preference for learning arithmetic sequences at school